Potential Beneficial Effects of Granulocyte Colony-Stimulating Factor Therapy for Spastic Paraparesis in a Patient with Kyphoscoliosis: A Case Report - Sienkiewicz, Dorota; Kułak, Wojciech; Okurowska-Zawada, Bożena; Wojtkowski, Janusz; Paszko-Patej, Grażyna; Dmitruk, Elżbieta; Kalinowska, Anna; Okulczyk, Kamila (Neuropediatrics, 2014)
Congenital kyphosis and kyphoscoliosis are much less common than congenital scoliosis and more serious because these curves can progress rapidly and can lead to spinal cord compression and paraplegia. A 15-year-old boy presented with congenital kyphoscoliosis along with spastic paraparesis (American Spinal Injury Association Impairment Scale grade C). We examined the safety and effectiveness of a low dose of analog granulocyte colony-stimulating factor (G-CSF) in this patient. G-CSF 5 µg/kg was given subcutaneously, daily for 5 days per month for 3 months. Laboratory tests, including blood, biochemical tests, and CD34+ cells (marker hematopoietic progenitor cells) were performed, in addition to clinical examination. Clinical examination revealed an increase of muscle strength in the upper limbs and decrease spasticity in the lower limbs between baseline and day 90 and day 180. We found no serious adverse event, drug-related platelet reduction, or splenomegaly. Leukocyte levels remained below 21,000/µL. CD34+ increased significantly at day 5 of G-CSF administration. Low-dose G-CSF was safe and well tolerated by the patient. A significant increase in muscle strength in this patient with spastic paraparesis after 3 months of treatment may indicate beneficial effects of G-CSF factor in this disorder. These results are inspiring and warrant further studies.
Keywords: boy; congenital kyphoscoliosis; spastic paraparesis; granulocyte colony-stimulating factor; CD34+; muscle strength